Effects of Bojungikgi-tang on anorexic patients with atopic dermatitis: A protocol for a randomized, usual care-controlled, assessor-blinded, parallel, pilot clinical trial. Issue 9 (4th March 2022) - Lee, Boram; Park, Hyo-Ju; Jung, So Young; Kwon, O-Jin; Ko, Mi Mi; Jeong, Hyun Ah; Jung, Jeeyoun
Abstract: Background: Anorexia and atopic dermatitis (AD) are highly prevalent diseases, and the herbal medicine Bojungikgi-tang (BJT) has been frequently used for the treatment of both anorexia and AD. However, no study has simultaneously evaluated the effects of BJT for both anorexia and AD. Methods: A prospective, randomized, usual care-controlled, assessor-blinded. parallel, pilot clinical trial has been designed to explore the feasibility, preliminary effectiveness, and safety of BJT for the treatment of anorexic patients with AD. Forty anorexic patients with AD will be randomly assigned (1:1) to BJT or the usual care group. The BJT group will be administered BJT granules twice a day for 8 weeks and followed up for 4 weeks whereas the usual care group will not receive BJT granules. All participants in both groups will be provided with over-the-counter topical corticosteroids as a relief drug. Data will be collected at baseline and at 4, 8, and 12 weeks after randomization. The primary outcome is the score on the anorexia visual analog scale at 8 weeks post-treatment. The secondary outcomes include body weight, body fat percentage, body fat mass, skeletal muscle mass, SCORing of Atopic Dermatitis index, Validated Investigator Global Assessment scale for Atopic Dermatitis, Dermatology Life Quality Index, EuroQoL 5 Dimension 5 Level, deficiency and excess pattern identification questionnaire, total immunoglobulin E, eosinophil count, and frequency and amount of use of topical corticosteroids. Adverse events and laboratory test results will be monitored to assess safety. Fecal samples to check for gut microbiome changes and blood samples to check immune and metabolic markers will be collected before and after taking BJT. Discussion: This is the first trial that explores the preliminary effectiveness and safety of BJT for the treatment of anorexic patients with AD. The results of this pilot study will provide the basic evidence for large-scale, confirmatory, multicenter, high-quality clinical trials. Trial registration: Clinical Research Information Service, KCT0006784 (registered on November 26, 2021).